Evaluasi Kesesuaian Lahan untuk Tanaman Cabai Merah (Capsicum annuum L.) di Kecamatan Tabongo Kabupaten Gorontalo - Arifka Mutmainah; Muhammad Arief Azis; Indriati Husain (Transbahasa, 2025)
In Tabongo District, the harvested area for red chili plants remained constant at 1 hectare from 2019 to 2020. However, there was a significant decline in production, as evidenced by the red chili yield, which reached 27,200 kg in 2019 but dropped drastically to only 700 kg in 2020. This study aims to (1) analyze the land characteristics and quality in Tabongo District, Gorontalo Regency, and (2) determine the land suitability class for red chili cultivation in the area. The research was conducted using a survey method and land suitability matching criteria for red chili plants. The results indicate that the land characteristics and quality in the study area generally contain adequate soil nutrients. The actual land suitability for red chili cultivation in Tabongo District is predominantly classified as S3 (marginally suitable) with an area of 1,003.44 hectares. Meanwhile, the potential land suitability is mainly classified as S2 (moderately suitable) with a total area of 954.67 hectares.